Design of fixed-pitch variable-speed wind turbine controller - Chen, Weiran. (2009)
Wind energy is the fastest-growing renewable energy resource in modern era. Horizontal-axis wind turbine is the most commonly adopted device in converting part of kinetic energy of the wind into useful mechanical energy, and ultimately electrical energy. Control plays a critical role in modern wind energy conversion systems (WECS); it enables the optimal use of the turbine capacity as well as the alleviation of aerodynamic and mechanical loads that reduces the lifespan of the apparatus. Within the multiple goals of controlling of WECS, power optimization is one of the most sophisticated tasks due to anonymous wind speed, together with other electrical or mechanical constrains. The most classical control methodology, PID control law is adopted and tested in this project. The controller monitors the power output of the motor generator and serves as feedback for the system to produce an optimal rotor speed. In the system, the pitch angle was set to be fixed. Based on the simulation results, the designed PID controller is found to be reasonably successful, while limitations are also discussed.